Application of antimicrobial peptides in plant protection: making use of the overlooked merits - Tang, Rui; Tan, Hui; Dai, Yan; Li, Lin’ai; Huang, Yan; Yao, Huipeng; Cai, Yi; Yu, Guozhi (Frontiers in Plant Science, 2023)
Pathogen infection is one of the major causes of yield loss in the crop field. The rapid increase of antimicrobial resistance in plant pathogens has urged researchers to develop both new pesticides and management strategies for plant protection. The antimicrobial peptides (AMPs) showed potential on eliminating plant pathogenic fungi and bacteria. Here, we first summarize several overlooked advantages and merits of AMPs, which includes the steep dose-response relations, fast killing ability, broad synergism, slow resistance selection. We then discuss the possible application of AMPs for plant protection with above merits, and highlight how AMPs can be incorporated into a more efficient integrated management system that both increases the crop yield and reduce resistance evolution of pathogens.